The Effect of Wordwall Media on Improving Critical Thinking Skills of Grade IV Students in Science IPAS Learning at SDN Inpres Kombo - Nurhaidah, Nurhaidah; Istiqamah, Nur; Ziaulhaq, Muhammad (FKIP - Universitas Riau, 2025)
This study aims to determine the effect of Wordwall media on improving the critical thinking skills of fourth-grade students in Integrated Science and Social Studies (IPAS) at SDN Inpres Kombo. The background of this study is the low critical thinking ability of students, indicated by difficulties in analyzing problems, formulating solutions, and providing logical reasons. This condition is worsened by the predominantly conventional teaching methods, which results in low student engagement during the learning process. This study employed a quasi-experimental method with a one-group pretest-posttest design. The sample consisted of 18 students, including 10 females and 8 males, selected through saturated sampling. The instrument used was a 10-item multiple-choice test based on Ennis's critical thinking indicators: basic clarification, decision-making fundamentals, inference, advanced clarification, and strategy/tactics. Data analysis involved descriptive and inferential statistics (paired sample t-test). The results showed a significant increase in the students' average scores from the pretest to the posttest. The t-test significance value of 0.000 < 0.05 indicates that Wordwall media has a significant effect on improving students' critical thinking skills and can be an effective, interactive, and enjoyable learning innovation in elementary schools.